2020
DOI: 10.3390/electronics9101599
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Spiking Neural Networks Based on Binary Streamed Rate Coding

Abstract: Spiking neural networks (SNN) increasingly attract attention for their similarity to the biological neural system. Hardware implementation of spiking neural networks, however, remains a great challenge due to their excessive complexity and circuit size. This work introduces a novel optimization method for hardware friendly SNN architecture based on a modified rate coding scheme called Binary Streamed Rate Coding (BSRC). BSRC combines the features of both rate and temporal coding. In addition, by employing a bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Figure 13 shows the case when the applied input image is ‘7’, the SNN predicts the correct classification result of ‘7’ by producing the maximum spiking activity at the 7th output node. The average classification accuracy achieved for the SNN is 94.66%, which is very close to the accuracy of 94.69% for the optimized SNN model in Python [ 41 ].…”
Section: Performance Analysismentioning
confidence: 53%
See 1 more Smart Citation
“…Figure 13 shows the case when the applied input image is ‘7’, the SNN predicts the correct classification result of ‘7’ by producing the maximum spiking activity at the 7th output node. The average classification accuracy achieved for the SNN is 94.66%, which is very close to the accuracy of 94.69% for the optimized SNN model in Python [ 41 ].…”
Section: Performance Analysismentioning
confidence: 53%
“…For the SNN implementation proposed in this paper, the SNN model for the MNIST dataset is first optimized using a low-cost spike signal representation technique called Binary Streamed Rate Coding (BSRC), which was presented in our previous work [ 41 ]. While the proposed SNN employs the off-chip training technique, it determines the SNN’s floating point weights by propagating sequences of spikes through an accurate model of the target SNN chip, instead of an ANN counterpart as in most other SNNs.…”
Section: Snn Implementation and Circuit Designmentioning
confidence: 99%
“…The proposed SNN SoC architecture adopts a spike signal representation called Binary Streamed Rate Coding (BSRC), which has been introduced by [ 18 ]. It has been shown that BSRC allows for an optimized SNN model for compact hardware and employs direct training for high accuracy based on an off-chip training technique.…”
Section: Neural Network Architecturementioning
confidence: 99%
“…[29] downsized SNN models by 73.78% with low-precision parameters at the cost of 1.04% test error increase. Other works showed potential of low-precision SNNs on various object recognition datasets [1,27,39].…”
Section: Spiking Neural Networkmentioning
confidence: 99%
“…For successful deployment to neuromorphic chips, this integration in deep SNNs is inevitable and more important than in ANNs. However, most of the studies, unlike those of ANNs, have focused on quantization [1,27,29,39] and pruning [20,30] in deep SNNs. This is because knowledge distillation indispensably requires training procedure, which is challenging in deep SNNs.…”
Section: Introductionmentioning
confidence: 99%